Reflective gas cell structure for spectroscopic carbon dioxide sensor - Salim, Mohd. Rashidi (2016)
This thesis describes an optical gas sensing system suitable for monitoring the presence of carbon dioxide (CO2). An optical gas sensor using low cost and compact mid-infrared components has been developed and tested. The emitter and detector are compact, inexpensive and have low power consumption when compared with devices typically used in gas spectroscopy. Simulators such as ZEMAX®12 and SpectralCalc.com are primarily used in this work. Firstly, the research focuses on the simulation of the optimized and low cost gas cell for improvement using ZEMAX®12. Few gas cell structures have been designed and analyzed, which include Single-Input-Single-Output (SISO), 2-Multi-Input-Single-Output, 4-Multi- Input-Single-Output (4-MISO) and 8-Multi-Input-Single-Output. Of all these structures, SISO achieves the highest power efficiency of 28.028%. However, sensitivity analysis has shown that 4-MISO yields the highest sensitivity of - 0.2879%-1 and -0.2895%-1 for concentration range from 1.5% to 1.8% and from 1.1% to 2.0% respectively. Secondly, the optomechanical design of optimized 4-MISO was analyzed and fabricated using low cost and robust material. Experimental works were then carried out and the sensor’s output was acquired and recorded using Data Acquisition card and LabVIEW programme. Experimental results show that the new developed 4-MISO sensor has similar sensitivity to simulated gas sensor for detecting carbon dioxide gas concentration range from 1.5% to 1.8% with overall sensitivity of -0.2916%-1. However, the deviation of sensitivity between the measured and simulated range of concentration was calculated at 0.0037%-1. Finally, the developed low cost sensor has shown the capability of detecting CO2 gas concentration with high accuracy of 0.6357% and response time of less than 1 second. The optimized gas sensor can be applied in various potential applications such as in monitoring indoor air quality, automotive, horticulture and heating, ventilating and air conditioning systems.